Examining the Impact of Supervisory Performance, Principal Leadership, and Work Environment on Islamic Religious Education Teachers Performance West Lombok Elementary Schools - Akhmad Sujai; Adi Fadli; Subki Subki; Ridwan Mas'ud (STAI Hubbulwathan Duri, 2025)
This study investigates the influence of supervisory performance, the principal’s managerial role, and the work environment on the performance of Islamic Religious Education (PAI) teachers in Islamic elementary schools in West Lombok. Enhancing teacher performance is critical for improving the quality of Islamic education. A total of 138 PAI teachers were selected using a simple random sampling technique. Data were collected through a structured questionnaire and analyzed using descriptive statistics, multiple regression analysis, and partial correlation analysis. Findings indicate that supervisory performance, the principal’s managerial role, and the work environment significantly affect teacher performance, as reflected by an F-value of 6.866 and a significance level of 0.000 (p 0.05). The combined variables explained 37.5% of the variance in teacher performance, while the remaining 62.5% was influenced by other factors. Among managerial aspects, the informational and service roles contributed significantly, with R² changes of 11.5% and 16.9%, respectively. Improving teacher performance can be achieved by strengthening supervisory practices, enhancing principals’ managerial roles—particularly in informational and service capacities—and fostering a supportive work environment. This research contributes to the field of Islamic education by providing empirical evidence on key organizational factors influencing PAI teacher performance. The findings offer practical implications for school leadership and policy to support effective Islamic educational practices.